Secondary headaches in pregnancy and the puerperium - Khoromi, Suzan (Frontiers in Neurology, 2023)
Headache during pregnancy can be due to primary causes such as migraine but can also be a presenting symptom of secondary causes including life threatening conditions. This is a minireview of secondary causes of headache during pregnancy and the puerperium. Unique alterations in physiological and vascular functions as well as in the coagulation pathway which occur during pregnancy increase the risk of most of these secondary conditions which include preeclampsia, eclampsia, hemorrhagic stroke, cerebral venous, sinus thrombosis, reversible cerebral vascular syndrome, and posterior reversible encephalopathy. Marked increase in progesterone level in pregnancy is also associated with the growth of tumors such as meningiomas, as 70% of these tumors are positive for progesterone receptors and increase in size can lead to headache along with other neurological symptoms. Hemodynamic changes can lead to the growth of meningiomas as well. Although hormone producing pituitary tumors are usually not conducing to pregnancy, women with known pituitary tumors who do get pregnant may become symptomatic during pregnancy and develop secondary headache. Another rare cause of secondary headache during pregnancy is pituitary apoplexy. Although its occurrence is uncommon, it needs to be properly recognized and treated to avoid endocrine and visual complications. Other rare entities with increased incidence during the puerperium such postdural puncture headache will be also discussed. In summary, new onset headache during pregnancy deserves special attention because in the absence of proper recognition and treatment, secondary headache disorders can endanger the life of the mother and the fetus.